Promoting future teachers’ evidence-informed reasoning scripts: Effects of different forms of instruction after problem-solving - Krause-Wichmann, Theresa; Greisel, Martin; Wekerle, Christina; Kollar, Ingo; Stark, Robin (Frontiers in Education, 2023)
Pre-service teachers face difficulties when dealing with problem situations in the classroom if their evidence-informed reasoning script (EIRS) is not adequately developed. An EIRS might be promoted by demonstrating how to implement evidence-informed reasoning after a problem-solving activity on an authentic case. However, it is unclear what form of instruction is appropriate to promote pre-service teachers in the development of an EIRS. The present 2×3-factorial experimental intervention study investigated how different forms of instruction on functional procedures (example-free vs. example-based) and on dysfunctional procedures (without vs. example-free vs. example-based) affect the development of an EIRS. N = 384 pre-service teachers worked on a written case vignette of a problem situation in a problem-solving phase, in which the crucial steps of the EIRS were prompted externally. In the subsequent instruction phase, the participants compared their own solution with an example-free or example-based instruction on functional procedures, which was either supplemented by an example-free or example-based instruction on typical dysfunctional procedures or not at all. The participants’ learning success (declarative EIRS; near and far transfer problem-solving performance) and error awareness were assessed. The results revealed that the example-based instruction on functional procedures led to a higher learning success than the example-free instruction. Both forms of instruction on dysfunctional procedures improved learning success compared to learning without one. During learning, error awareness was higher for learners who worked with an example-free instruction on dysfunctional procedures. In order to promote the development of an EIRS in pre-service teachers, it is promising to provide instruction after problem-solving that presents a functional example of evidence-informed reasoning for the given problem and that also points out typical dysfunctional approaches to solving the problem. The results highlight the importance of selecting appropriate scaffolds in case-based learning approaches that aim to develop cognitive schemata. The mechanisms that explain when and why instructions on dysfunctional procedures work need to be further explored.